Yhwh’s Unique Speaker: Jeremiah - Georg Fischer (Religions, 2025)
In Jer 15:19, Yhwh calls the prophet Jeremiah “my mouth”. This unique designation highlights his importance and finds support in several other features: Jeremiah is portrayed as the promised successor to Moses (Jer 1:7, 9), opposes all other contemporary prophets (e.g., Jer 20; 23; 26–29), and has many additional roles and activities. Furthermore, he shares traits with Yhwh’s servant from Isa 49 and 53. His ‘biography’ is extraordinary and is shown at length, unusual for the Latter Prophets, ranging from before his birth (Jer 1:5) to his disappearance in Egypt (Jer 43–44). His ‘confessions’ in Jer 11–20 testify to immense suffering and have become models for personal prayer. Like the prophet, his scroll is unique, too. No other biblical writing deals so extensively with trauma, exemplified at the downfall of Jerusalem in 587 BC, its roots, and its impact. This even leads to an uncommon structure of the scroll, ending with disaster in Jer 52, whereas all other scrolls of prophets contain hope as conclusions. Jer stands out with the analysis of guilt as cause for the catastrophe, yet it conveys also consolation, especially in Jer 29–33. In these chapters, elements for a renewed society emerge, corresponding to the name of the prophet, which signifies “Yhwh will raise up”. The real source for this change lies in the way Jer conceives the biblical God. No other writing in the Bible tells about his weeping, as a sign of helplessness vis-à-vis the continuing resistance of his people. Many prayers in the scroll, including the confessions, focus on the importance of an intimate, personal relationship with him, going beyond traditional piety in several aspects; Moshe Weinfeld has called them “spiritual metamorphosis”. The singularity of Jer applies also to its literary features. Its mixtures of poetry and prose, of divine and human speaking, of narratives about the prophet in first and third person are a challenge for every reader, as well as the ‘unordered’ chronology and retarded information. Jer excels in the use of other scrolls; the degree of intertextuality and the way of combining motifs from ‘foreign’ sources in a synthetic way are outstanding. To grasp fully its message requires familiarity with more than half of what later became the Hebrew Bible.